The Jailed Coiling Technique for the Treatment of Penetrating Ulcers and Saccular Aneurysms of the Aortic Arch. (July 2020) - Silverberg, Daniel; Bar-Dayan, Avner; Rimon, Uri; Raskin, Daniel; Fefer, Paul; Halak, Moshe
Objective: To evaluate the technical success and short-term outcome of patients with penetrating aortic ulcers (PAUs) and saccular aneurysms (SAs) of the aortic arch treated with the jailed coiling technique. Methods: A retrospective review of 9 patients (mean age 70 years, 9 males) treated for PAUs and SAs of the aortic arch between 2018 and 2019 at our institution. Treatment included thoracic endovascular aneurysm repair (TEVAR) with a short (1cm) proximal landing zone, followed by coiling of aneurysm through a jailed extraluminal catheter. Results: All 9 patients underwent TEVAR followed by jailed coiling of the lumen of the aneurysms. Debranching of supra-aortic vessels was performed in 4 patients in order to create a proximal landing zone of at least 10 mm. Technical success was achieved in all cases. Coils were placed accurately within the aneurysm lumen in all patients. No distal embolization occurred. One patient expired in the perioperative period from a cardiac event. No patient developed spinal cord ischemia or stroke in the perioperative period. Mean follow-up was 10 months (range 3-18). On follow-up imaging, complete thrombosis of the aneurysm lumen was seen in all patients. None experienced enlargement of ulcer dimensions and none required reintervention. Conclusion: PAUs and SAs of the aortic arch with a very short landing zone can be treated successfully by jailed coiling of the aneurysm and TEVAR. The procedure is technically feasible and can be performed with minimal morbidity. Long-term durability of the repair needs to be determined.